Surface band bending and carrier dynamics in colloidal quantum dot solids. Issue 42 (20th October 2021) - Clark, Pip C. J.; Lewis, Nathan K.; Ke, Jack Chun-Ren; Ahumada-Lazo, Ruben; Chen, Qian; Neo, Darren C. J.; Gaulding, E. Ashley; Pach, Gregory F.; Pis, Igor; Silly, Mathieu G.; Flavell, Wendy R.
Abstract : Evidence for band bending in colloidal quantum dot (CQD) solids is shown using photoemission surface photovoltage measurements, and carrier dynamics for a range of CQD solids are measured, correlating the results to surface chemistry. Abstract : Band bending in colloidal quantum dot (CQD) solids has become important in driving charge carriers through devices. This is typically a result of band alignments at junctions in the device. Whether band bending is intrinsic to CQD solids, i.e. is band bending present at the surface–vacuum interface, has previously been unanswered. Here we use photoemission surface photovoltage measurements to show that depletion regions are present at the surface of n and p-type CQD solids with various ligand treatments (EDT, MPA, PbI2, MAI/PbI2 ). Using laser-pump photoemission-probe time-resolved measurements, we show that the timescale of carrier dynamics in the surface of CQD solids can vary over at least 6 orders of magnitude, with the fastest dynamics on the order of microseconds in PbS–MAI/PbI2 solids and on the order of seconds for PbS–MPA and PbS–PbI2 . By investigating the surface chemistry of the solids, we find a correlation between the carrier dynamics timescales and the presence of oxygen contaminants, which we suggest are responsible for the slower dynamics due to deep trap formation.